2017
DOI: 10.1073/pnas.1712934114
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptive evolution in novel environments acts as an architect of population range expansion

Abstract: Colonization and expansion into novel landscapes determine the distribution and abundance of species in our rapidly changing ecosystems worldwide. Colonization events are crucibles for rapid evolution, but it is not known whether evolutionary changes arise mainly after successful colonization has occurred, or if evolution plays an immediate role, governing the growth and expansion speed of colonizing populations. There is evidence that spatial evolutionary processes can speed range expansion within a few gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 56 publications
11
118
0
Order By: Relevance
“…Prober et al (2015) discuss a number of possible ways to select source populations for assisted migration. Assisted migration could slow range expansions by disrupting spatial sorting and local adaptation, as demonstrated in three lab experiments (conducted under idealized conditions) that reshuffled individuals within a range (Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017. Assisted migration could slow range expansions by disrupting spatial sorting and local adaptation, as demonstrated in three lab experiments (conducted under idealized conditions) that reshuffled individuals within a range (Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017.…”
Section: Conservation Implicationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Prober et al (2015) discuss a number of possible ways to select source populations for assisted migration. Assisted migration could slow range expansions by disrupting spatial sorting and local adaptation, as demonstrated in three lab experiments (conducted under idealized conditions) that reshuffled individuals within a range (Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017. Assisted migration could slow range expansions by disrupting spatial sorting and local adaptation, as demonstrated in three lab experiments (conducted under idealized conditions) that reshuffled individuals within a range (Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017.…”
Section: Conservation Implicationsmentioning
confidence: 81%
“…Natural selection can favor individuals with higher fecundity or dispersal ability on the expanding range front because range-front populations are often released from intra-and inter-specific tradeoffs that constrain this evolution in the range center (Burton et al 2010, Gilman et al 2010, Phillips et al 2010a, Svenning et al 2014. Lab experiments also demonstrate dispersal evolution during range expansion and suggest evolution of dispersal and population growth rate can occur in three to four generations under idealized lab conditions (Fronhofer and Altermatt 2015, Williams et al 2016, Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017, Van Petegem et al 2018. Lab experiments also demonstrate dispersal evolution during range expansion and suggest evolution of dispersal and population growth rate can occur in three to four generations under idealized lab conditions (Fronhofer and Altermatt 2015, Williams et al 2016, Ochocki and Miller 2017, Szűcs et al 2017, Weiss-Lehman et al 2017, Van Petegem et al 2018.…”
Section: Single Species Eco-evolutionary Dynamics Cool Range Marginsmentioning
confidence: 99%
“…For example, several studies have found evidence consistent with inbreeding depression in natural invading populations and its rescue by admixture (Bailey & McCauley, ; Keller et al, ; Mullarkey, Byers, & Anderson, ; Nolte, Gompert, & Buerkle, ; Rius & Darling, ; van Kleunen et al, ). It may be that founding populations with particularly low genetic variation and high genetic load, which would be predicted to benefit most from admixture, are relatively rare across species introductions as a whole, although admixture could provide substantial benefits to founding populations when severe genetic bottlenecks do occur, and these benefits may be realized over evolutionary time, which is not readily observed in experimental crosses (Szűcs et al, ; Szűcs, Melbourne, et al, ; Szűcs, Vahsen, et al, ; Wagner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As population abundances increase and reduce the efficacy of adaptive traits, populations may undergo declines but recover once the expression of adaptive traits is no longer dampened by density‐dependent regulation. Presently, we are unaware of studies that investigate how density dependence and adaptation may interact to affect population dynamics under climate change scenarios, but similar dynamics may occur at the edges of species range expansions (Szűcs et al, ).…”
Section: Discussionmentioning
confidence: 99%